2016
DOI: 10.1007/s10439-016-1680-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method of Weighting Cumulative Helmet Impacts Improves Correlation with Brain White Matter Changes After One Football Season of Sub-concussive Head Blows

Abstract: One football season of sub-concussive head blows has been shown to be associated with subclinical white matter (WM) changes on diffusion tensor imaging (DTI). Prior research analyses of helmet-based impact metrics using mean and peak linear and rotational acceleration showed relatively weak correlations to these WM changes; however, these analyses failed to account for the emerging concept that neuronal vulnerability to successive hits is inversely related to the time between hits (TBH). To develop a novel met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…A number of neuroimaging studies have reported significant findings in WM changes based on DTI after only one season in athletes without concussions [Bazarian et al, ; Davenport et al, ; Koerte et al, ; Lao et al, ; Merchant‐Borna et al, ; Myer et al, ]. Our findings in Season 1 were based on a cohort of 10 athletes in the noncollar group and 13 athletes in the collar group, and replicated findings reported in our prior work in which larger cohorts (including the athletes in this study) were used in the analysis [Myer et al, ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A number of neuroimaging studies have reported significant findings in WM changes based on DTI after only one season in athletes without concussions [Bazarian et al, ; Davenport et al, ; Koerte et al, ; Lao et al, ; Merchant‐Borna et al, ; Myer et al, ]. Our findings in Season 1 were based on a cohort of 10 athletes in the noncollar group and 13 athletes in the collar group, and replicated findings reported in our prior work in which larger cohorts (including the athletes in this study) were used in the analysis [Myer et al, ].…”
Section: Discussionsupporting
confidence: 86%
“…The effects of cumulative head impacts on young athletes over their entire careers are still unknown. Emerging neuroimaging investigations have generated evidence that suggests that the brain network may be affected, both structurally and functionally, during one season of contact sports, even with only nonclinical, subconcussive head impacts being tracked [Bahrami et al, ; Bazarian et al, ; Davenport et al, ; Lao et al, ; Koerte et al, ; Merchant‐Borna et al, ; Myer et al, ; Yuan et al, in press). When taken in aggregate over the career of the athlete, repetitive SCI could potentially increase the risk of season (or career) ending injuries, neurological impairments, and WM alterations [Bahrami et al, ; Myer et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is becoming clearer that multiple mild TBIs associate with a high risk of chronic traumatic encephalopathy (CTE), a dementia with distinctive clinical and pathologic features (Shively et al, 2012; Gardner and Yaffe, 2015). Additionally, there is evidence that sub-concussive head blows can induce acute brain changes as evaluated by imaging (Breedlove et al, 2012; Bazarian et al, 2014; Merchant-Borna et al, 2016), changes in neurochemistry (Lin et al, 2015) and cognitive function (McAllister et al, 2012), although the long-term consequences of these changes remain to be determined. Data from our gene array studies in rodents support a link between mild concussive and blast TBI and dementia as well as Parkinson’s disease, illustrated by the identification of gene sets and pathways associated with AD and Parkinson’s disease observed by Day 3 and 14 after injury (i.e., Blalock a1 Alzheimer’s disease incipient; Alzheimer’s disease dn and up and Parkin pathway (Tweedie et al, 2013a; Tweedie et al, 2016; Tweedie et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…Subconcussive impacts are defined as events similar to those giving rise to a concussion, or mild traumatic brain injury (mTBI), but apparently involving insufficient impact forces or accelerations to produce symptoms associated with mTBI (Shuttleworth-Edwards et al, 2008). Many contact sports, including American football, soccer, rugby, boxing, wrestling, and lacrosse, result in rather high numbers of repetitive head impacts throughout a season and career, with football having been observed to lead possibly to thousands of subconcussive impacts for a single player over the course of one season (Merchant-Borna et al, 2016, Talavage et al, 2014). …”
Section: Introductionmentioning
confidence: 99%